Design and development of novel 1,2,3-triazole chalcone derivatives as potential anti-osteosarcoma agents via inhibition of PI3K/Akt/mTOR signalling pathway - Su Qing; Xu Baolin; Tian Zhoubin; Gong Ziling (Acta Pharmaceutica)
Osteosarcoma (OS) is an uncommon tumour that mainly affects bone in children and adolescents. The current treatment options of OS are of limited significance due to their immense side effects. In the present manuscript, we have developed a novel series of 1,2,3-triazole chalcone derivatives as potential agents against OS. The compounds were synthesized and evaluated for their PI3K and mTOR inhibitory activity using luminescent kinase assay, and Lance ultra assay, resp. The entire set of compounds showed significant to moderate inhibition of both kinases in the nanomolar range. The three most active compounds: 4e (N-(4-(3-(1-(4-bromophenyl)-1H-1,2,3-triazol-4-yl)acryloyl)phenyl)-4-nitrobenzamide), 4f (N-(4-(3-(1-(4-bromophenyl)-1H-1,2,3-triazol-4-yl)acryloyl)phenyl)-4-chlorobenzamide) and 4g (4-bromo-N-(4-(3-(1-(4-bromophenyl)-1H-1,2,3-triazol-4-yl)acryloyl)phenyl)benzamide), were evaluated for anticancer activity against human OS cancer cell line (MG-63), liver cancer cell line (HepG2), lung cancer cell line (A549) and cervical cancer (HeLa), using MTT assay. Among the tested series, compound 4e showed a better inhibitory profile than gedatolisib against PI3K and was approximately comparable to that of gedatolisib against mTOR. The most significant inhibitory activity was observed for compound 4e against all cell lines (MG-63, HepG2, A549 and HeLa), still somewhat lower to comparable to that of gedatolisib, but with the highest potency against MG-63 cells. Compound 4e was further tested for anti-cancer activity against other OS cells and showed to be equipo-tent to gedatolisib against U2OS and Saos-2 cells. Moreover, it was also found non-toxic to normal cells (BEAS-2B and MCF 10A). The effect of compound 4e was further determined on apoptosis of Saos-2 cells by Annexin-PI assay, where it significantly amplified the percentage of apoptotic cells. Novel 1,2,3-triazole chalcone derivatives are potential agents against OS.